A new name for the oviraptorid dinosaur “Ingenia” yanshini (Barsbold, 1981; preoccupied by Gerlach, 1957) - Easter, Jesse (Zootaxa, 2013)
The genus name of the small oviraptorid dinosaur Ingenia yanshini is preoccupied by the tripyloidid nematode Ingenia mirabilis, thus making the former a junior homonym of the latter. Although “Ingenia” yanshini is sympatric with Conchoraptor gracilis, it is distinguished from Conchoraptor by proportions of the manus. It also differs appreciably from the ingeniines Heyuannia huangi and Nemegtomaia barsboldi in manual and pelvic proportions. “Ingenia” yanshini is not referable to any other taxon, and is renamed Ajancingenia yanshini gen. nov. Several specimens originally referred to this species have subsequently been transferred to new genera, and the taxonomic assignment of material referred to Ajancingenia yanshini gen. nov. is reassessed.